HEALTH PROMOTION IN THE ELDERLY: A PROPOSAL FOR PHYSICAL ACTIVITY FOR PEOPLE WITH HIGH BLOOD PRESSURE (Fiep Bulletin - online, 2015)
This article is top priority to identify how physical education professionals and the areas involved with the Promotion of Health, can help seniors with Hypertension through practice-oriented Daily Physical Activity. These can be effective and bring a large benefit to health, obtaining an exponential increase in your quality of life from the moment that they happen to be supporters of frequent activities in your day-to-day. With this, members of the third age attain even greater longevity and may even enjoy the pleasures of life, and a way to prevent chronic diseases effectively, through the exertion itself. The research was conducted with thirty elderly practicing Physical Fitness and Activities in Social Projects of bodily practices to seniors through the Quality of Life questionnaire (SF-36, 2010). And he sought also detect through Association of Ideas Common, what these seniors think about inducing words. This technique is advocated by Cunha (2012) and seeks to identify concepts of the social imaginary of these actors from the first three words that come to memory. It is interesting to perceive themselves as the elderly can make an analogy between words carry Hypertension, Health, Physical Activity and Quality of Life. This becomes evident when analyzing-what were their responses when asked about such matters. It was found that the words Health, Disease Prevention, Provision, Wellness, Quality of Life were repeated several times.
Keywords: Elderly. Physical Activity. Hypertension.